2009
DOI: 10.1200/jco.2008.19.2435
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Trial of Tremelimumab in Patients With Metastatic Melanoma

Abstract: Multiple infusions of tremelimumab were generally tolerable and demonstrated single-agent antitumor activity. Both phase II regimens generated durable tumor responses. Based on its more favorable safety profile, 15 mg/kg every 3 months was selected for further clinical testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
198
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(207 citation statements)
references
References 23 publications
7
198
0
2
Order By: Relevance
“…Interestingly, 10mg/kg was the MTD identified in the first-in-human study of tremelimumab 9 and ultimately this dose was found to be more tolerable when dosed at a frequency of every 3 months. 10 We found no evidence that CP-870,893 aggravated tremelimumab-associated toxicity or vice versa, nor did a new spectrum of autoimmunity emerge.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Interestingly, 10mg/kg was the MTD identified in the first-in-human study of tremelimumab 9 and ultimately this dose was found to be more tolerable when dosed at a frequency of every 3 months. 10 We found no evidence that CP-870,893 aggravated tremelimumab-associated toxicity or vice versa, nor did a new spectrum of autoimmunity emerge.…”
Section: Discussionmentioning
confidence: 59%
“…Although each mAb has been tested separately and shown single-agent activity in patients with advanced melanoma, 7,8 the combination has not. Tremelimumab is a fully human IgG2 anti-CTLA-4 mAb that produced clinical activity 8-10 similar to ipilimumab, although it did not improve OS when compared to chemotherapy in a randomized phase III study. 8 CP-870,893 is a fully human IgG2 agonist mAb evaluated in a single-dose study, a weekly infusion study, and studies combining CP-870,893 with chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, comparisons of growth rates of PAN02 tumors in different strains of mice were affected by the presence of lymphocytes and the amount of host Ido1 expression: tumor doubling is fastest in immunodeficient mice and slowest in Ido1 −/− mice. 2 These data also suggest that a lack of host Ido1 activity can, to some extent, impede tumor growth. Finally, we have shown that TILs are more prevalent and more active after treatment with an IDO1 inhibitor.…”
Section: Discussionmentioning
confidence: 81%
“…Suppressive mechanisms in place to rein in normal immune responses may be usurped by tumor cells to limit the effectiveness of antitumor responses (8). Interference with two of these, CTLA4 and the PD1/PDL1 axis, is currently being tested clinically and providing a similar low-frequency but durable benefit to patients (2,3,9). Another such mechanism under investigation is tryptophan depletion through enhanced indoleamine-2,3-dioxygenase (IDO) activity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the effective and global coverage of metastatic cells represents a critical factor for optimizing therapeutic outcome. Although novel targeted therapies such as BRAF inhibitors (Yang et al, 2010) and anti-CTLA4 antibodies (Camacho et al, 2009) are showing promising results in melanoma clinical trials, resistance to these compounds and patient relapse are rapidly emerging (Poulikakos et al, 2010). Small interfering RNA-mediated therapies, such as targeting BCL2 with the antisense oligonucleotide Oblimersen (Jansen et al, 2000), also had limited success.…”
Section: Introductionmentioning
confidence: 99%